Private security and domestic violence: the risks and benefits of private security companies working with victims of domestic violence - Harkin, Diarmaid (Routledge studies in crime and society, 2020)
Why now? The recent emergence of private security companies into the field of domestic violence -- Case study examples of security companies working with victims of domestic violence in Australia -- The damaging impacts of unethical and incompetent private security companies -- The risks and benefits of the 'technical solutions' offered by private security companies -- The benefits for victims and domestic violence services of using private security companies -- How should private security companies be regulated for the optimal benefit of victims of domestic violence?